INTEGRATING ETHNOSCIENCE TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS: SYSTEMATIC LITERATURE REVIEW - Nuryati, Tutuk; Istianah, Farida; Suryanti, Suryanti (Jurnal Konseling Pendidikan Islam, 2026)
21st-century science education demands the development of critical thinking skills. However, field realities, such as observations at SDN Dungkek I, indicate that learning remains dominated by textbook dependence without contextual modification. This leads to low student engagement and an inability to connect scientific concepts with local culture. This study aims to analyze the potential and effectiveness of integrating ethnoscience into science modules to improve students' critical thinking skills. The study employs a descriptive qualitative method using a Systematic Literature Review (SLR) approach based on Cooper's (2016) model. Data were collected from accredited databases such as Google Scholar, DOAJ, and GARUDA, and analyzed using Miles and Huberman’s techniques. The review results demonstrate that ethnoscience integration has a significant positive impact across educational levels: at the primary level (SD), it helps visualize abstract concepts into concrete ones; at the junior secondary level (SMP), it trains students to verify myths versus scientific facts; and at the senior secondary level (SMA), it strengthens argument evaluation and complex data interpretation. It is concluded that ethnoscience-based learning, particularly when combined with Problem-Based Learning (PBL) or Deep Learning models, effectively transforms students into active learners capable of valid scientific reasoning and inference based on local wisdom.